Tongue gangrene and oropharyngeal carcinoma - Girardi, Fabio Muradás; Rech, Eduardo Lange; França, Victória Teles; Roman, Luiz Inácio (Clinical and Biomedical Research, 2016)
Gangrene of the tongue is a condition rarely described in the literature. It generally occurs in association with temporal arteritis and other vasculitides. We described a rare case of tongue necrosis associated with oropharyngeal carcinoma. A 67-male patient, previously submitted to exclusive radiotherapy for a squamous cell carcinoma of the tonsillar region, was admitted to our service with high dysphagia. Computed tomography showed circumferential swelling of the oropharynx, with areas of diffuse contrast uptake and significant reduction of the vascular flow at this level, especially venous return. About 6 months after the onset of symptoms, he was submitted to an urgent tracheostomy for airway obstruction. Then, about 1 month after tracheotomy, the neck skin became ecchymotic, congested, and he started with profuse oropharyngeal bleeding and congestion and thrombosis signs in the tongue. To our knowledge, this entity has not been yet described in the literature. Keywords: Oropharyngeal neoplasms; tongue; thrombosis